Integrated approaches to phosphorus management in the Watton Brook, UK. Issue 1 (27th February 2022) - Simpson, Hannah; Knightbridge, James; Nineham, Nicola
Abstract : Phosphorus enrichment in waterbodies can increase the risk of eutrophication and be detrimental to the health of dependent ecosystems. Phosphorus is a common reason for a waterbody failing to meet the Water Framework Directive 'good' status. The Watton Brook (Norfolk, UK) is required to meet good status by 2027; it currently has an overall 'moderate' status and a 'poor' status for phosphate (as of 2016 classification). Source apportionment modelling predicts treated effluent from water recycling centres is the primary phosphorus source to the Watton Brook, followed by significant agricultural contributions. Considering the agricultural sector input and the cost of upgrading sewage treatment, this study took a stakeholder- and ecosystem services-led approach to explore catchment-based solutions. The feasibility for an integrated catchment approach builds on detailed environmental conceptualisation, phosphorus source apportionment ground-truthing and a review of potential costs and benefits. By combining Farmscoper, SIMCAT-SAGIS InVEST modelling and an ecosystem services assessment, the study targeted solutions to reduce phosphorus loading while delivering multiple benefits. The feasibility and natural capital enhancement focus of a phosphorus balancing scheme in the Watton Brook ensures that the proposed solutions are cost-beneficial for both the wastewater company and its customers while offering wider benefits for the environment and the local community.